3D-bioprinted alginate-based bioink scaffolds with β-tricalcium phosphate for bone regeneration applications - Yi-Fan Wu; Ya-Ting Wen; Eisner Salamanca; Lwin Moe Aung; Yan-Qiao Chao; Chih-Yun Chen; Ying-Sui Sun; Wei-Jen Chang (Journal of Dental Sciences, 2024)
Background/purpose: 3D-printed bone tissue engineering is becoming recognized as a key approach in dentistry for creating customized bone regeneration treatments fitting patients bone defects requirements. 3D bioprinting offers an innovative method to fabricate detailed 3D structures, closely emulating the native bone micro-environment and better bone regeneration. This study aimed to develop an 3D-bioprintable scaffold using a combination of alginate and β-tricalcium phosphate (β-TCP) with the Cellink® BioX printer, aiming to advance the field of tissue engineering. Materials and methods: The physical and biological properties of the resulting 3D-printed scaffolds were evaluated at 10 %, 12 %, and 15 % alginate combined with 10 % β-TCP. The scaffolds were characterized through printability, swelling behavior, degradability, and element analysis. The biological assessment included cell viability, alkaline phosphatase (ALP) activity. Results: 10 % alginate/β-TCP 3D printed at 25 °C scaffold demonstrated the optimal condition for printability, swelling capability, and degradability of cell growth and nutrient diffusion. Addition of β-TCP particles significantly improved the 3D printed material viscosity over only alginate (P < 0.05). 10 % alginate/β-TCP enhanced MG-63 cell's proliferation (P < 0.05) and alkaline phosphatase activity (P < 0.001). Conclusion: This study demonstrated in vitro that 10 % alginate/β-TCP bioink characteristic for fabricating 3D acellular bioprinted scaffolds was the best approach. 10 % alginate/β-TCP bioink 3D-printed scaffold exhibited superior physical properties and promoted enhanced cell viability and alkaline phosphatase activity, showing great potential for personalized bone regeneration treatments.